The Magnitude-Optimum Design of the PI Controller for Plants with Dead Time and Oscillatory Modes - Cvejn, Jan (Elsevier Science BV, 2024)
The design of the PI controller for stable linear plants based on the magnitude-optimum criterion can be applied directly for high-order linear models with dead time, without need of the model reduction. This paper discusses key properties of this method, especially considering oscillating plants. Even though the closed-loop response is specified only for low frequencies and the robustness requirements are not explicitly formulated in the design objective, in the case of plants without zeros a large closed-loop stability margin is ensured automatically regardless the dead time value, under the assumption that the damping coefficients corresponding to the oscillatory modes of the plant are sufficiently high.
Návrh PI regulátoru pro systémy s dopravním zpožděním a kmitavými módy metodou optimálního modulu
Keywords: dead time; time delay; frequency response; magnitude optimum; PI controller; PID controller; process control; stability margin; dopravní zpoždění; časové zpoždění; frekvenční odezva; optimální modul; PI regulátor; PID regulátor; řízení procesů; rezerva ve stabilitě